Readiness of Educational Institutions in Bekasi Regency to Face Society 5.0 - Jefferson Benyamin; Hikmat Zakkky Almubaroq (Department of Political Science - Universitas Sains Al-Qur’an, 2022)
Society 5.0 is part of a revolution that does not only focus on technology, but focuses on humans as the main object. Educational institutions in forming Human Resources must be ready to face the era of society 5.0, as well as what happened to educational institutions in Bekasi Regency. This study will discuss the readiness and efforts that can be made by educational institutions in Bekasi Regency in facing the era of society 5.0. This study uses a qualitative method with a literature study approach where the data sources used are journals, articles, books and other relevant sources. Based on the results of the study, it was concluded that currently educational institutions in Bekasi Regency are not ready due to various factors such as inadequate facilities and the quality of Human Resources that has not been maximized. Therefore, the recommendations that can be made by educational institutions are to provide education and training to educators, make standard learning models, and hold competitions to recruit the best talents in the field of technology mastery.